V33. Functional imaging of somatosensory finger representation and intracortical inhibition modulation in complex regional pain syndrome. Issue 8 (August 2015) - Strauss, S.; Grothe, M.; Usichenko, T.; Byblow, W.; Lotze, M.
<x xml:space="preserve">Abstract</x> Neurophysiological pathology in CRPS type I is characterized by somatosensory and motor deficits. Transcranial magnetic stimulation (TMS) and functional MRI reveal decreased short intracortical inhibition (SICI) and smaller representation distance in the hand region of primary somatosensory cortex (S1) between the first and fifth digit in CRPS. Interestingly, an application of anesthetic cream to the forearm increases spatial tactile resolution (STR) and also SICI of hand muscles in healthy participants. As such, this intervention might be suited to reverse pathologic findings in CRPS patients and tested this in a double blinded placebo controlled study. In addition we used high spatial resolution fMRI of the thumb (D1) and pinky (D5) S1 BA 3b representation before and after intervention. Patients showed decreased STR over D1 (tip of thumb) on their affected side if compared to the unaffected side (t = 2.31; p < 0.05). STR improved after anesthetic cream (t = 3.0; p < 0.05) but not after placebo application. Pain intensity was not modulated after intervention. SICI was increased only after analgesic cream (t = 2.22; p < 0.05) but not after placebo. We expect an association of D1–D5 distance and STR in our fMRI-data. In conclusion, temporary deafferentation of an area neighboring the CRPS-affected region can modulate neuropathological characteristics of CRPS and might be a promising strategy for therapeutic interventions.